Design Visual Elements and Brand-Based Equity: Mediating Role of Green Concept - Li, Ying (Frontiers in Psychology, 2022)
Although benefits of design perception has been documented from the perspective of consumers at large but the perspective of employees has been ignored at large. This study tends to add into body of knowledge by investigating the impact of design element on employee brand based equity under the mediating role of green concept. For this purpose data has been collected from the employees of manufacturing sector and a data of 346 respondents has been used for inferential purpose. This data was collected under survey research method through convenience sampling technique. Data has been analyzed through Smart-PLS by applying structural equation modeling technique. After assessing the measurement and structural model, results indicate that design elements of products in manufacturing industry can influence the employees’ perception and it can foster positive behavior among employees in the shape of employee brand based equity. Mediating role of green concept has also been proved. Limitations and future directions are also discussed.